2016
DOI: 10.1016/j.ejrnm.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of chest ultrasound with color Doppler in diagnosis of pneumonia in adults

Abstract: Objective: To evaluate the role of color Doppler sonography in comparison with CXR and CT imaging in diagnosis of pneumonia in adults. Patients and methods: Thirty-one patients with clinical suspicion of pneumonia were assessed by chest radiography, CT and sonography. Quantitative and qualitative sonographic examination of lesions was performed using color Doppler imaging. The correlation between color Doppler and CT findings was determined. Results: Lung ultrasound showed high sensitivity (100%), specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, false positives are related to the heterogeneity of the sonographic pattern shown by lung lesions ( 21 , 22 ). Some authors have indicated the possibility of distinguishing necrotic areas from other unspecific anechoic areas within a consolidation through the Doppler study of the vascular pattern ( 31 ). However, this parameter may not be considered a reliable sign of distinction, because of the presence of “flash artifacts” (i.e., a burst of color signal caused by motion of transducer or the patients' breathing) in most patients ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, false positives are related to the heterogeneity of the sonographic pattern shown by lung lesions ( 21 , 22 ). Some authors have indicated the possibility of distinguishing necrotic areas from other unspecific anechoic areas within a consolidation through the Doppler study of the vascular pattern ( 31 ). However, this parameter may not be considered a reliable sign of distinction, because of the presence of “flash artifacts” (i.e., a burst of color signal caused by motion of transducer or the patients' breathing) in most patients ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoechoic areas have a "tissue-like appearance" or "hepatization" in LUS with small hyperechoic [bronchograms] or hypoechoic (fluid bronchograms) structures within them point toward pneumonia and are described as consolidations and can appear with free fluid [pleural effusion] [7, [13][14][15][16][17]. Pleural effusions in COVID-19 are rare and can be seen in bacterial superinfections or other diseases such as heart failure [9,12,18,19].…”
Section: Consolidations and Pleural Effusionmentioning
confidence: 99%
“…Monophasic blood flow is found in bronchial arteries. This can be help detect complications such as necrosis, by visualizing hypoechoic areas with no blood flow [36,37].…”
Section: Covid-19 Pneumoniamentioning
confidence: 99%